Cross-Cultural Analysis of the Role of Traditional Medicine in Health Access in Indonesia - Abdullah, Vera Iriani; Wahidin, Wahidin; Wibowo, Diki Prayugo; Mariani, Ria (Westscience Press, 2023)
This study investigates the contribution of traditional medicine on health care access in Indonesia through a quantitative cross-cultural approach. Utilizing a sample of 350 individuals that is diverse in terms of age, gender, and ethnic background, the study investigates the prevalence and characteristics that impact the use of traditional medicine. The findings show that traditional healing methods are heavily relied upon, especially by elderly people and members of specific ethnic groups. The necessity for culturally responsive healthcare practices is highlighted by the discovery that cultural beliefs are important determinants of health-seeking behaviour. The results add to the growing body of knowledge about the integration of traditional medicine into modern healthcare systems by highlighting the significance of customizing therapies to the many cultural settings found throughout Indonesia.